2019
DOI: 10.2507/30th.daaam.proceedings.146
|View full text |Cite
|
Sign up to set email alerts
|

The Mobility of Robotised Work Cells in Manufacturing

Abstract: Many companies are already using robots, but many have not found enough applications for the robot and therefor they have not purchased it jet. One robot can be used to perform several different tasks, but it also raises the question of whether the production needs to be reorganized so that these multiple tasks are directed to the robot, or it can be solved differently where the robot moves between different tasks. In this paper different concepts will be discussed and each of its disadvantages and advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In earlier work on robotised work cells [3], the reasons were found that prevent SMEs from adopting robots, and various variants of robot implementation in enterprises were proposed [3]. It was found that the best solution for SMEs is to obtain a robot that can be moved from one job position to another at the factory level, and this should be done with an automated mobile robot.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier work on robotised work cells [3], the reasons were found that prevent SMEs from adopting robots, and various variants of robot implementation in enterprises were proposed [3]. It was found that the best solution for SMEs is to obtain a robot that can be moved from one job position to another at the factory level, and this should be done with an automated mobile robot.…”
Section: Resultsmentioning
confidence: 99%
“…Mostly these are SMEs for whom buying a robot is a big investment and the investment has to pay back within a reasonable time. One of the reasons for not using a robot, according to a previous study [3], is the insufficient applicability of the robot in one working position. The company may not have enough work for the robot in one particular position in order to derive as much benefit from it as is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant literature has analysed the need for mobility generated by industrial robots [8,4] and identified possible solutions for it. The solutions for moving a robot manually by a human or automatically by a mobile robot were evaluated in [8]. The automatic positioning accuracy of the robot arm moved by the mobile robot was analysed using machine vision [4].…”
Section: Introductionmentioning
confidence: 99%